METAFORA KEHEWANAN DALAM NOVEL NICHOLAS SPARK 'A WALK TO REMEMBER' - Gracia Otta (Jurnal Lazuardi, 2021)
Imagination of the author was very broad, that affects the impressions and imagination, where the readers were forced to have a free imagination in finding out the meanings and differences of each literary sentences. Using figurative language makes the novel more interesting also challenging to read, and the reades are pleased to imagine about the story based on the illustration. This article was conducted to identify and to describe the animal metaphors in literary sentences that contained in A Walk To Remember novel and to describe the meaning dennotatively and connotatively of each literary sentences. Descriptive qualitative method was applied since the data presented in the form of language. The data were collected through reading and identifying the metaphors found in the novel. The results of this study showed eight items of animal metaphors.